PHYSICAL ACTIVITY AS A THERAPEUTIC STRATEGY FOR CANCER-RELATED COGNITIVE IMPAIRMENT - A REVIEW - Anna Szot; Jędrzej Sztajura; Monika Bujak; Katarzyna Chowaniec-Rybka (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: After cardiovascular diseases, malignant tumors are the second most common cause of death, disability, and reduced quality of life. Cancer-related cognitive impairment (CRCI) encompasses transient or persistent cognitive dysfunction, either subjectively reported by patients or objectively confirmed through neuropsychological testing. The aim of this study is to discuss the current state of knowledge and research on the impact of non-pharmacological interventions, especially the impact of various forms of physical activity (aerobic, strength, mixed) on the cognitive functions of cancer patients during and after treatment. Materials and Methods: A comprehensive literature search was conducted using the PubMed, BioMed Central, Scopus, and Google Scholar databases. Keywords included: physical activity, cognitive function, cancer survivors, quality of life, chemotherapy, and cancer-related cognitive impairment. References cited within selected articles were also reviewed. Studies from the past 10 years were analyzed, applying carefully defined inclusion and exclusion criteria. This review presents the latest clinical evidence and current strategies for the management of cancer-related cognitive impairment. Conclusions: CRCI is a prevalent condition among cancer patients, significantly impacting their quality of life and overall well-being. Cognitive dysfunction may arise from various cancer therapies, not solely chemotherapy. The findings underscore the need for systematic monitoring of cognitive function in oncology patients, along with the integration of preventive and rehabilitative measures into comprehensive care plans. Early detection of CRCI and the implementation of cognitive rehabilitation and physical activity interventions are crucial for improving patient outcomes.